1977
DOI: 10.1111/j.1467-8624.1977.tb01173.x
|View full text |Cite
|
Sign up to set email alerts
|

Training Disadvantaged Preschoolers on Various Fantasy Activities: Effects on Cognitive Functioning and Impulse Control

Abstract: Preschool children were trained in 1 of 3 different types of fantasy activities over a school year. The effects of this training were evaluated over a variety of tasks measuring cognitive development and impulse control. The same basic experiment was replicated over 3 different years. Results indicated that physical enactment of fantasy experiences (viz., acting fairy tales or enacting previous experiences) had a sizable effect on many of these variables; while simply listening and discussing was often no more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
3
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 7 publications
3
70
3
1
Order By: Relevance
“…For example, some perspective-taking tasks require specific experimental procedures, such as role playing or videotape watching, that are often logistically complex and time consuming (e.g., Chandler, 1973;Saltz, dixon, & Johnson, 1977). For example, some perspective-taking tasks require specific experimental procedures, such as role playing or videotape watching, that are often logistically complex and time consuming (e.g., Chandler, 1973;Saltz, dixon, & Johnson, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some perspective-taking tasks require specific experimental procedures, such as role playing or videotape watching, that are often logistically complex and time consuming (e.g., Chandler, 1973;Saltz, dixon, & Johnson, 1977). For example, some perspective-taking tasks require specific experimental procedures, such as role playing or videotape watching, that are often logistically complex and time consuming (e.g., Chandler, 1973;Saltz, dixon, & Johnson, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the youngsters in the play trained group showed significantly more imaginative play actions than those in the control on these behaviors and on the posttest. The ability to play imaginatively is necessary for cognitive growth (Piaget, 1962) and can be nurtured by adults working with young children and by school programs and child development philosophies (Saltz, Dixon, & Johnson, 1977;Smilansky, 1968). Cohen and Tomlinson-Keasey (1968) showed that the greatest quantity of exploratory play developed during parentchild interaction settings rather than in other settings, such as child alone.…”
Section: Resultsmentioning
confidence: 99%
“…Going a bit further into the cognitive realm, Saltz, Dixon, and Johnson (1977) examined the role of fantasy in delay of gratification. They found that children who were instructed to think about their favorite story while waiting performed better in delay tasks than did those who were not.…”
Section: Behaviorist Accounts (Social-cognitive Branch) Of Delay Of Gmentioning
confidence: 99%